A study on the fungi isolated from the carpeting, walls and Holy Qurans from the Blue Mosque and Little Hagia Sophia Mosque situated in the province of Istanbul - Cesuroğlu, Özlem; Çolakoğlu, Günay Tülay (My University, 2017)
In this study the sampling of microfungus content from the carpeting, walls and Holy Qurans of two different mosques in the province of Istanbul was undertaken and in order to determine quantities. Samples were taken in 2015 during the months of January, April, July and October. The samples were taken with non-agar based sterile swabs and were then taken to the laboratory. Throughout the duration of the study, 17 species belonging to 9 genera were isolated and a total of 193 colonies were examined. Throughout the study the most commonly isolated microfungus genus was Aspergillus at 52.9%. This genus was followed by Penicillium at 26.5%, Cladosporium at 7.8%, Alternaria at 4.7%, Chaetomium at 2.6%, Trichoderma at 3.2%, Mucor at 1.1% and Eurotium and Rhizopus 0.6%. Throughout the duration of the study the most isolated species of microfungus was Aspergillus fumigatus at 25.9%. This species was followed by Aspergillus flavus at 9.8%, Penicillium palitans at 9.3%, Aspergillus niger at 8.3%, Penicillium citreonigrum at 7.8%, Penicillium solitum at 6.3%, Aspergillus sydowii at 5.2%, Alternaria alternata and Cladosporium sphaerospermum at 4.7%, Aspergillus parasiticus at 3.7%, Trichoderma longibrachiatum at 3.2%, Penicillium citrinum and Cladosporium cladosporioides at 3.1%, Chaetomium globosum at 2.6%, Mucor sp. at 1.1%, and finally Eurotium herbariorum and Rhizopus stolonifer at 0.6%.
Keywords: Aspergillus; Penicillium; fungus; carpet; mosque; Istanbul